The Role of Classes for Pregnant Women in Improving the Attitudes of Pregnant Women Towards Preventing Stunting - Risqi Utami; Hafizah Che Hassan; Nur Syazana Umar (International Journal of Public Health, 2024)
This systematic review examines the effectiveness of antenatal classes in improving pregnant women's attitudes towards stunting prevention. The review analyzed 28 studies published between 2018 and 2023, focusing on developing countries, particularly in Southeast Asia. The methodology followed PRISMA guidelines, utilizing multiple academic databases. The analysis revealed that structured antenatal classes significantly improved maternal knowledge about stunting (68% increase in knowledge scores) and led to positive behavioral changes in nutritional practices. Regular attendance at comprehensive antenatal classes was associated with better pregnancy outcomes, with participants showing 75% higher rates of implementing recommended nutritional guidelines. Key success factors included regular class frequency, interactive teaching methods, cultural sensitivity, and strong community support. However, significant challenges were identified, including resource limitations, access barriers, and cultural resistance. The review highlighted successful adaptations such as hybrid learning models and community-based approaches. Recommendations include strengthening program design through evidence-based approaches, enhancing community engagement, developing sustainable funding mechanisms, and implementing robust monitoring systems. This review underscores the vital role of antenatal classes in stunting prevention while emphasizing the need for continued research to address existing challenges and enhance program effectiveness across diverse settings.